The Effect of Consumer Brand Involvement on Brand Advocacy: A Moderated Mediation Model of Brand Affect and Perceived Value in an Emerging Market Context - Rukaiyah, St.; Safar, Ilham; Arief, Abdul Samad (International Review of Management and Marketing, 2026)
This study investigates the effect of consumer brand involvement on brand advocacy by examining the mediating role of brand affect and the moderating role of perceived value within the culinary industry in Makassar, Indonesia, as a representative of an emerging market context. Using a survey of 272 consumers, the data were analyzed with structural equation modeling–partial least squares (SEM-PLS). The results reveal that consumer brand involvement significantly enhances brand affect, which in turn fosters stronger brand advocacy. Moreover, brand affect mediates the relationship between brand involvement and advocacy, confirming the centrality of emotional mechanisms in driving consumer advocacy. Conversely, the moderating role of perceived value was not supported, suggesting that emotional attachment outweighs rational value considerations in shaping advocacy within hedonic and culturally embedded consumption contexts. This study extends the stimulus–organism–response (SOR) framework and Brand Equity Theory by demonstrating the dominance of affective mechanisms over cognitive evaluations in emerging markets. It also fills a research gap by examining brand advocacy in the culinary sector, which has been underrepresented compared to studies on luxury or durable goods. From a managerial perspective, the findings suggest that culinary brands in emerging markets should prioritize strategies that strengthen emotional and cultural engagement—such as storytelling, experiential marketing, and community involvement—rather than relying solely on functional value propositions.